KEKUATAN MENGIKAT ASEAN MUTUAL LEGAL ASSISTANCE TREATY (AMLAT) BAGI NEGARA ANGGOTA ASEAN DALAM RANGKA PENEGAKAN HUKUM KEJATAN TRANSNASIONAL - Indira Devitasari (Faculty of Law Universitas Sebelas Maret, 2015)
This research is conducted to get a legal argumentation related of the binding force in ASEAN Mutual Legal Assistance Treaty (AMLAT) for ASEAN member countries. The question will be answered by determining the norms and principles of international law binding force. The sources of this research are international conventions, doctrine, customary international law, national law in some countries and other publications related to the binding force in AMLAT. The legal sources collected by study documentation and interviews are analyzed by interpretation and content analysis. The result show that the binding force in AMLAT based on the theory of natural law and theory of positive law. There are some obligations set out in article 1 , 4 , 9 , 10 , 11 , 13 , 14 , 16 , 17 , 18 , 20 , 22 AMLAT which has jurisdiction closure and different legal systems that is not working as enforcement mechanism for transnational crimes.